Beyond the UN global compact institutions and regulations - Leonard, Liam.; Gonzalez-Perez, Maria-Alejandra. (Bingley, U.K. : Emerald, 2015)
This book offers African, Asian, Latin American, European, and North American perspectives on institutions and regulations promoting sustainable economic growth in the post-2015 development agenda in areas such as environment, labour, risk management, corporate social responsibility, corporate governance, and innovation. The chapters address sustainability issues at the firm, national, regional and international levels from a multidisciplinary perspective. The chapters of this volume address the challenge of enhancing economic competitiveness of the supply side economies while pushing a sustainable development agenda. This work addresses the existing inequalities, environmental degradation, and economic/financial instability under current dynamics of international and domestic power relations in order to meet the set objectives for the post-2015 era. This volume advances the perspectives on the non-compulsory alternative to markets regulations, the United Nations Global Compact, explored in the previous volume 'The UN Global Compact: Fair Competition and Environmental and Labour Justice in International Markets' vol. 16.
The global compact : corporate sustainability in the post 2015 world / Maria Alejandra Gonzalez-Perez, Liam Leonard -- International business risk management and the emerging market crises as challenges for the UN Global Compact / Sylwia Starnawska -- The institutionalization of CSR : at the crossroads of home and host countries institutional settings, multinational corporations and multinational institutions / Annie Lamontagne -- Incorporating voluntary standards into national law : an overview of the scandinavian experience / John McNally -- Corporate impact on the environment and the judicial development of the norm of corporate sustainability : implications for the implementation of the UN Global Compact / Olawale Ajai -- Sustainable Processes and Production Methods (PPMs) in private standards : a proxy for trade barriers or decentralised mechanisms for environmental governance? / Maria Alejandra Calle -- Environmental sustainability in the CAFTA-DR Region : impact of the treatys environmental provisions on country and multinational firm level sustainability / Dinorah Frutos-Bencze -- IFRS adoption and the environment : is Africa closing her eyes to something? / Uchenna Efobi -- Innovation-driven economic development model : a way to enable competitiveness in Nigeria / Stephen Oluwatobi -- Governments as owners : nationalization of international business and social responsibility / Maria Alejandra Gonzalez-Perez, Santiago Sosa -- Public management and smart mobs despite the 2014 FIFA World Cup in Brazil : reflections on the contemporary organizational model in comparison with the UN Global Compact initiative / Carlos Otávio Afonso, Ricardo Cavalcante -- Trade openness, financial liberalization, economic growth, and environment effects in the North-South : new static and dynamic panel data evidence / Xiuping Hua, Agyenim Boateng -- Labour relations and international business : the doctrine of constructive dismissal and labour relations in Malaysia / Balakrishnan Muniapan.
Includes bibliographical references.
Print version record
Keywords: Nature -- Environmental Conservation & Protection; Social impact of environmental issues; Economic development -- International cooperation; Sustainable development